Porous structure and adsorption properties of magnesium silicates synthesized by three routes - M. V. Kravchenko; L. S. Kuznetsova; A. V. Terebilenko; M. M. Tsyba; I. V. Romanova (Хімія, фізика та технологія поверхні)
The aim of presented work was to synthesize the ecologically friendly sorbents using low cost reagents based on magnesium silicates by precipitation, hydrothermal and sol-gel methods. Morphology of materials obtained was investigated by means of thermogravimetric analysis (TG-DTA), low temperature adsorption/desorption method, scanning and transmission electron microscopic studies (SEM and TEM). It has been found that all sorbents are obtained in a form of amorphous layer-structure magnesium silicates with the micro- and mesoporous structure. Based on low temperature nitrogen isotherms, the specific surface area and volume of micropores calculated by the Brunauer-Emmet-Teller (BET) and Barrett-Joyner-Halenda (BJH) methods were the greatest for the sample obtained by sol gel method (SBET = 640 m2/g, Vmicro = 0.26 cm3/g) while the sample synthesized by precipitation had the biggest volume of mesopores among the materials investigated (Vmeso = 0.39 cm3/g). As follows from TEM images, all samples consist of particles with the size from 10 up to 50 nm, the sample synthesized by sol gel method had the most homogeneous structure (MgSi-3). The ion exchange capacities of materials in the process of Cs+, Sr2+, Cu2+, and Co2+ removing from aqueous solution were determined and it was found that these properties depend on the method of materials obtaining. Data showed that magnesium silicate synthesized by precipitation method has the higher capacity toward the heavy metal cations compared to the radionuclides (1.56 and 0.96 mmol/g for cobalt and copper, respectively). For two samples synthesized by hydrothermal and sol-gel methods the increasing was fixed of capacity towards cesium and strontium ions that could be explained by the significant amounts of pores approx 2.6 nm radii in their structure. Experimental data were fitted to the Langmuir models. Analysing the data of adsorption studies, it was noted that all materials obtained can be used in adsorption technology for purification of water from heavy metal ions and radionuclides.